In Brief: Mitophagy: mechanisms and role in human disease. Issue 3 (29th September 2016) - Springer, Maya Z; Macleod, Kay F
Abstract: Mitophagy is a selective form of macro‐autophagy in which mitochondria are specifically targeted for autophagic degradation. Mitophagy plays an important role in cellular homeostasis by eliminating dysfunctional mitochondria and reducing mitochondrial mass as an adaptive response to stress. Cells execute mitophagy through several non‐redundant mechanisms, including the PINK1/Parkin partnership, which modulates turnover of depolarized mitochondria, and stress‐induced BNIP3, NIX, and FUNDC1 molecular adaptors, which interact directly with LC3 to promote mitophagy. These pathways are deregulated in human diseases, including cancer, neurodegeneration, metabolic disorders, muscle atrophy, ageing, and inflammation, reflecting the importance of mitophagy as a cellular housekeeping function. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.